The performance of an acoustic levitator. (April 2020) - Hsu, C H; Lin, H Y; Agarwal, A; Davis, I; Nolan, K P; Lua, K B
Abstract: An acoustic levitator uses an array of ultrasonic transducers to generate a standing acoustic pressure field which exerts a radiation force on small particles, allowing the particles to be trapped, relocated, separated or combined. Experiments on levitating particles of different densities and calculations of the acoustic radiation force and moment have been reported in the literature. However, direct inspection on the acoustic pressure field pattern is seldom carried out. This paper reports an investigation on the performance of an existing acoustic levitator design, which uses off-the-shelf components, by comparing the visualized pressure field from Schlieren imaging to analytical simulations. The ability to compare Schlieren imaging results to analytical simulations readily can prove to be a vital tool. Since the simulations provide an ideal pressure field, the imaging of the levitator pressure field can highlight discrepancies between the real and ideal cases. This can be especially useful as a diagnostic tool to identify the cause of a drop in performance of the acoustic levitator in a real world scenario.